Family Dynamics./How Men Construct Masculinity and Position Themselves Within the Family. - Kalavrytinou Maria - Eleni; Louka Penelope (2015)
Introductiom, Methodology, Design, Materials, Participants, Procedure, Analysis, Dynamic Standing of Masculinity, Family: Widespread Beliefs about Masculinity, Blurred Distinction Between the Roles in the Family, Readjustment of the New Sense of Fatherhood, Interview Schedule, Combined Spider Graph, Table 1Q Combined Spider Graph, Interviews, Briefing, Consent Form PDP, Conclusion, References, Appendix.